THORACIC LIPOSARCOMA IN AN END STAGE RENAL DISEASE PATIENT - Ishtiaq, Rizwan; Naeem, Arslan; Ratnani, Iqbal (Journal of Ayub Medical College Abbottabad, 2019)
Liposarcoma arising in the thoracic cavity is a rare entity. It is usually found in the retroperitoneal space and the extremities. No case of thoracic liposarcoma in a patient suffering from the end-stage renal disease has been reported in the literature. We herein present the first case of thoracic liposarcoma in a patient suffering from the end-stage renal disease. Metabolic disturbances, increased use of erythropoietin and increased diagnostic workup attributes to greater risk of cancer in patients suffering from renal failure. A chemotherapeutic drug, Trabectedin has been approved for advanced liposarcoma. Prognosis of such tumours depends on the size, location, and their histological subtype. Keyword: End-stage renal disease, Erythropoietin, Liposarcoma, Thoracic cavity, Trabectedin